Between the processes of strengthening and weakening of the Family Health Strategy - Regina Stella Spagnuolo; Silvia Cristina Mangini Bocchi (Associação Brasileira de Enfermagem, 2013)
This was a qualitative study with the purpose of designing a meta-model for the work process of the Family Health Strategy (FHS) team. It was based on the experience of six sample groups, composed of their members (physicians, professional nurses, dentists, dental assistants, licensed technical nurses and community health agents) in a city in São Paulo state, Brazil, totaling 54 subjects. Six theoretical models emerged from non-directive interviews. These were analyzed according to Grounded Theory and submitted to the meta-synthesis strategy, which produced the meta-model "between the processes of strengthening and weakening of the FHS model: professional-team-community reciprocity as an intervening component". When analyzed in light of the Theory of Complexity (TC), it showed to be a work with a vertical and authoritarian tendency, which is largely hegemonic in the tradition of public health care policies.